Optimizing Heat Flow for Sustainable Smoking: Dual-Heating System to Reduce Mangrove Consumption and Control PAH Contamination - Lidyana, Roslan; Annisa, Jamali; Abang Mohammad Nizam, Abang Kamaruddin; Ana Sakura, Zainal Abidin; Mohd Syahmi, Jamaludin (IEEE Malaysia, 2024)
Abstract— Mangrove overharvesting for firewood threatens the Irrawaddy dolphins’ habitat. Recently, automated smoking machines have been proven to reduce mangrove consumption. However, they are not user-friendly. Therefore, we proposed a modular smoking machine with dual heating sources based on practical considerations suggested by traditional smoked shrimp experts. This study showcases the optimization of heat flow in the design contributed by the two direct heating sources configured in an “L”-shape, i.e., one from the heater installed at the wall, and one from the smoking tray at the bottom of the insulated smoking chamber. Other notable modifications include the blower and chimney placement to that of the rotating tray and wall heater. Our work extensively discusses the evaluation of heat flow distributions, and particle movements to track the pathway of vapor and plausible Polycyclic Aromatic Hydrocarbons (PAH) contaminants. Computational fluid dynamic (CFD) outcomes corresponded positively with the experimental study. In the experiment, the smoker is fed hourly with 1 kg of mangrove firewood. After 5 hours, the drying and smoking process of smoke shrimps was completed when the moisture reduction reached 90% compared to the previous model, 70%, which saved up to 80% of mangrove consumption. Before the intervention, the traditional method consumed 20.79 kg per cycle. The optimized dual heating sourced smoking machine only needed 4 kg. CFD simulation demonstrated the uniform distribution of steam and heat flow contributed to this improvement. It is implicated that the well- controlled environment within the insulated smoking chamber stimulated firewood to form embers that radiate substantial consistent heat above 400°C resulting to the generation of PAH. Tests confirmed that the smoked shrimp samples contained an average of 0.2 mcg/ kg PAH, which is lower than, and adhere to the value of the European Commission standards at 2.0-12.0 mcg/kg.